Synthesis, optical and theoretical characterization of heteroleptic Iridium(III) Imidazo[1, 5-a]pyridine and -quinoline complexes. (September 2020) - Herr, Jasmin Martha; Rössiger, Carina; Locke, Harald; Wilhelm, Mikko; Becker, Jonathan; Heimbrodt, Wolfram; Schlettwein, Derck; Göttlich, Richard
Abstract: Blue OLEDs are still a challenge of today's photoelectrochemistry. The third generation of OLEDs is based on thermally activated delayed fluorescence (TADF). A series of heteroleptic iridium(III) imidazo[1, 5- a ]pyridine and -quinoline complexes with potential TADF behaviour was synthesized and characterized via UV–Vis absorption and fluorescence spectroscopy as well as measurements of the excited state lifetime. The experimental results were confirmed by computational calculations of the relative energy of the first excited singlet and triplet states. In addition, the HOMO and LUMO levels were calculated with DFT and compared to values estimated from redox potentials determined by cyclic voltammetry. For the first time, a TADF mechanism of these compounds has been proven. Graphical abstract: Image 1 Highlights: Ir-complexes of imidazo[1, 5-a]quinolines have been prepared fort he first time. The electrochemical and photochemical properties have been analyzed. For this type of complexes a TADF-mechanism of relaxation has been proven.